2021
DOI: 10.1371/journal.pone.0246142
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting soil bacterial counting methods: Optimal soil storage and pretreatment methods and comparison of culture-dependent and -independent methods

Abstract: Although a number of different methods have been used to quantify soil bacteria, identifying the optimal method(s) for soil bacterial abundance is still in question. No single method exists for undertaking an absolute microbial count using culture-dependent methods (CDMs) or even culture-independent methods (CIMs). This study investigated soil storage and pretreatment methods for optimal bacterial counts. Appropriate storage temperature (4°C) and optimal pretreatment methods (sonication time for 3 min and cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 45 publications
1
26
0
2
Order By: Relevance
“…type of cells and extraction protocols) and conditioned by a trade‐off with cell viability. These results agree with recent publications highlighting that step repetitions (re‐extractions) or stronger dispersion conditions could increase recovery but decrease cell viability (Lee et al, 2021; Ouyang et al, 2021). Our analysis of recovery efficiency was based on microscopy count, as this was the method most frequently used.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…type of cells and extraction protocols) and conditioned by a trade‐off with cell viability. These results agree with recent publications highlighting that step repetitions (re‐extractions) or stronger dispersion conditions could increase recovery but decrease cell viability (Lee et al, 2021; Ouyang et al, 2021). Our analysis of recovery efficiency was based on microscopy count, as this was the method most frequently used.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, we could not rule out the use of soil pre‐treatments before bacterial counts. All these factors could also contribute to the high variation detected for recovery efficiency estimates (Lee et al, 2021). However, even considering these constraints, our review revealed that recovery efficiency of native bacteria from soils is low (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine the number of microbial cells per gram of garden soil and model compost, aliquots (1 g) before and after the soil burial of textile samples were taken and the standard culture-dependent enumeration procedure was applied (Lawlor et al 2000;Lee et al 2021). Soil micro-organisms were also cultured at 30 °C on three types of agar media: Luria-Bertani agar (LA, Oxoid, UK) for heterotrophic bacteria; mannitol soy flower agar (MSF) (Hobbs et al 1989) for spore-forming bacteria; and Sabouraud dextrose agar (SAB, Difco, UK) for fungi.…”
Section: Microbial Cell Countsmentioning
confidence: 99%